2006
DOI: 10.1002/smll.200600135
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Poly(3,4‐ethylenedioxythiophene) Nanofibers from an Aqueous Surfactant Solution

Abstract: Easy does it: Poly(3,4‐ethylenedioxythiophene) (PEDOT) fibers can be synthesized from aqueous solutions of anionic surfactant by a self‐assembly method. This approach readily generates nanofibers with diameters down to about 10 nm and lengths of over 5 μm (see TEM image). The fibers can be produced with high yields and exhibit electrical conductivities of approximately 46 S cm−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 47 publications
3
139
0
1
Order By: Relevance
“…Some ligands can result in the formation of vesicles, micelles and coordination inorganic-organic nanomaterials with different morphologies in solution via coordination with metal ions. [25][26][27] These nanostructures are often used as precursors of metal oxide or soft templates of other nanomaterials. [28][29][30][31][32] From a fundamental viewpoint, it is highly desirable to understand the mechanism between metal ions and ligands because of their potential applications in the detection of metal ions, water treatment and drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Some ligands can result in the formation of vesicles, micelles and coordination inorganic-organic nanomaterials with different morphologies in solution via coordination with metal ions. [25][26][27] These nanostructures are often used as precursors of metal oxide or soft templates of other nanomaterials. [28][29][30][31][32] From a fundamental viewpoint, it is highly desirable to understand the mechanism between metal ions and ligands because of their potential applications in the detection of metal ions, water treatment and drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction peaks centered around 6.7°, 18.8°and 25.3°c orrespond to the (100), (300) and (400) planes of PEDOT, respectively [18]. The intense diffraction peak centered at 25.3°is attributed to the interchain planar ring-stacking distance [14]. It is observed that the sharpness of diffraction peaks increases with increasing SDS concentration, which is indicative of an increased periodicity of polymer chains.…”
Section: X-ray Diffraction Analysismentioning
confidence: 81%
“…One of the most salient features of EDOT is that the substitution at the 3-and 4-positions of thiophene ring prevents the occurrence of a-b and b-b coupling during polymerization, which results in more ordered polymer chains with longer conjugation lengths [13]. Han and Foulger [14] have reported the synthesis of PEDOT nanofibers by using SDS as surfactant; however, the effect of varying concentration of SDS on the electrical transport properties has not been systematically investigated. The electrical transport and magnetoresistance properties of PEDOT have been reported by different groups, Sangeeth et al [15], de Oliveira et al [16] and Aleshin et al [17]; however, the mechanism and the effect of disorder on these properties are not fully understood.…”
Section: Introductionmentioning
confidence: 98%
“…In both spectra, the absorption maximum located at about 600 nm is the characteristic of PEDOT, which is associated to the π→π* transition. [33,34] For the pure PEDOT prepared through a conventional emulsion technique, this broad band centered around 563 nm. For PEDOT/Ag nanocomposite, however, a slight red shift was observed.…”
Section: Uv/vis Absorption Spectroscopymentioning
confidence: 99%